A Storytelling Intervention in a Mobile, Web-Based Platform: A Pilot Randomized Controlled Trial to Evaluate the Preliminary Effectiveness to Promote Human Papillomavirus Vaccination in Korean American College Women. (April 2020) - Kim, Minjin; Lee, Haeok; Kiang, Peter; Aronowitz, Teri; Sheldon, Lisa Kennedy; Shi, Ling; Allison, Jeroan J.
Korean American women have substantially greater incidence rates of cervical cancer and the lowest rates of cervical cancer screening in the United States. However, there has been minimal research to promote human papillomavirus (HPV) vaccination among this population. A pilot randomized controlled trial was conducted to evaluate preliminary effectiveness of a storytelling video intervention using mobile, Web-based technology. One hundred and four Korean American college women were randomized to the experimental group (storytelling video) or the comparison group (information-based written material). The effects of the intervention were assessed immediately postintervention and at the 2-month follow-up. Both groups improved in knowledge of and attitude toward the HPV vaccine at the postintervention. At the 2-month follow-up, the experimental group was twice as likely to receive the HPV vaccine compared to the comparison group. This preliminary evidence supports the use of a storytelling video intervention and shows substantial promise for further development and testing in larger scale studies.